1990
DOI: 10.1901/jaba.1990.23-11
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Analysis and Extinction of Self‐injurious Escape Behavior

Abstract: Three studies are presented in which environmental correlates of self-injurious behavior were systematically examined and later used as the basis for treatment. In Study 1, 7 developmentally disabled subjects were exposed to a series of conditions designed to identify factors that maintain self-injurious behavior: attention contingent on self-injurious behavior (positive reinforcement), escape from or avoidance of demands contingent on self-injurious behavior (negative reinforcement), alone (automatic reinforc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

10
192
1

Year Published

1991
1991
2014
2014

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 266 publications
(204 citation statements)
references
References 33 publications
10
192
1
Order By: Relevance
“…Cataldo, 1990), it has also been found that some behavior problems persist in the absence of social consequences . Persons with severe developmental disabilities have been observed to engage in behaviors that appear to be maintained by directly (automatically) produced sensory consequences.…”
Section: Richard G Smith University Of North Texasmentioning
confidence: 99%
“…Cataldo, 1990), it has also been found that some behavior problems persist in the absence of social consequences . Persons with severe developmental disabilities have been observed to engage in behaviors that appear to be maintained by directly (automatically) produced sensory consequences.…”
Section: Richard G Smith University Of North Texasmentioning
confidence: 99%
“…Previous investigations have evaluated the efficacy of extinction procedures in the reduction of aberrant behavior (Lerman & Iwata, 1996). The use of extinction has been associated with a number of behavioral patterns including a temporary increase in response frequency (Iwata, Pace, Kalsher, Cowdery, & Cataldo, 1990) and extinction-induced aggression (Goh & Iwata, 1994). On a practical level, then, extinction procedures may be difficult or even dangerous to implement (Peck et al, 1996).…”
mentioning
confidence: 99%
“…When such a state of aversive stimulation exists and reinforcement (escape from the aversive stimulation) no longer results, we might expect to see severe, long-lasting extinction bursts coupled with other problem behaviors that have a history of producing escape because, as originally suggested by Skinner (1953, p. 150), the number of responses that occur during extinction may reflect the current strength of the relevant EO. Indeed, extended bursts during escape extinction have been reported in the literature Iwata, Pace, Kalsher, Cowdery, & Cataldo, 1990). Nonetheless such extinction bursts are often transitory (Iwata, Pace, Kalsher, Cowdery, & Cataldo, 1990) or are not reported (Lerman & Iwata, 1995).…”
Section: Analyzing Existing Treatments From An Eo Perspectivementioning
confidence: 91%
“…Indeed, extended bursts during escape extinction have been reported in the literature Iwata, Pace, Kalsher, Cowdery, & Cataldo, 1990). Nonetheless such extinction bursts are often transitory (Iwata, Pace, Kalsher, Cowdery, & Cataldo, 1990) or are not reported (Lerman & Iwata, 1995).…”
Section: Analyzing Existing Treatments From An Eo Perspectivementioning
confidence: 91%
See 1 more Smart Citation